2023
DOI: 10.21608/jnsbu.2023.278956
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Educational Program on Preventing Postpartum Depression among Mothers

Abstract: Background: Postpartum depression is a mood disorder that begins after childbirth and usually lasts beyond six weeks, in some cases up to a year. Aim: The study aimed to evaluate the effect of educational program on preventing postpartum depression among mothers. Design: A quasi experimental prepost test of two groups was used. Setting: This study was conducted in Obstetrics and Gynecological outpatient clinic at Benha university hospital. Sample: A purposive sample of 100 pregnant mothers. Tools: Three tools … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Similar to previous studies, we found interesting variations in the risks of PPD in younger age mothers, first-time mothers, mothers with two children, and mothers with more than three children [11,12]. These findings could be related to the lack of experience and awareness of the pressures of motherhood in new and first-time mothers, a lack of social support and the increased amount of care, work and mothering required as the number of children increases [12,16,28] and could be explored further. We also found a significant association between baby age and the risk of PPD, as those with babies under 6 months of age had a higher risk of depression (80% vs. 61%) compared to women whose babies were older.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to previous studies, we found interesting variations in the risks of PPD in younger age mothers, first-time mothers, mothers with two children, and mothers with more than three children [11,12]. These findings could be related to the lack of experience and awareness of the pressures of motherhood in new and first-time mothers, a lack of social support and the increased amount of care, work and mothering required as the number of children increases [12,16,28] and could be explored further. We also found a significant association between baby age and the risk of PPD, as those with babies under 6 months of age had a higher risk of depression (80% vs. 61%) compared to women whose babies were older.…”
Section: Discussionmentioning
confidence: 99%
“…These issues require further research to link women's integrative and preventive health policies and programs in order to improve reproductive health and maternal mental health [1][2][3]6,8,9,11,12,16,28]. Attention from primary care providers and other healthcare professionals and policymakers working in the reproductive and maternal health fields is also required [21,34,35].…”
Section: Study Implications and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation